Endocrine Mucin-Producing Sweat Gland Carcinoma: Case Presentation with a Comprehensive Review of the Literature - Gerardo Cazzato; Emilio Bellitti; Irma Trilli; Anna Colagrande; Nicoletta Sgarro; Vincenza Sara Scarcella; Teresa Lettini; Giuseppe Ingravallo; Domenico Piscitelli; Leonardo Resta; Lucia Lospalluti (MDPI AG, 2023)
(1) Background: Endocrine Mucin-Producing Sweat Gland Carcinoma (EMPSGC) is a rare, low-grade, neuroendocrine-differentiated, cutaneous adnexal tumor, officially recognized by the World Health Organization (WHO) Skin Tumors Classification in 2018 as a separate entity and homologue of endocrine ductal carcinoma in situ (eDCIS)/solid papillary carcinoma of the breast. Although it is more frequent in the female sex, between 60 and 70 years old, in the peri-orbital region, EMPSGC has also been described in the male sex, in subjects under 60 and over 80, and in extra-eyelid localizations (cheek, temple, scalp), but also in extra-facial localizations (chest and scrotum). (2) Methods: We present the clinical case of a 71-year-old woman with an undated lesion of the scalp, which presented as a nodule, skin-colored, and 2.5 cm in maximum diameter. We also conduct a comprehensive literature review from 1997 to the end of 2022, consulting PubMed, Scopus, Web of Science (WoS), and Google Scholar using the following keywords: "Endocrine mucin-producing sweat gland carcinoma" and/or "EMPSGC" and/or "skin" and "cutaneous neoplasms". In addition, we followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 253 patients were recorded; 146 were females (57.7%) and 107 were males (42.2%). The vast majority of the lesions were in the eyelids (peri-ocular region), and only a minority of cases involved the cheeks, supra-auricular, retro-auricular, and occipital region, with very rare cases in the scalp, to which the present is also added. (4) Conclusions: The morphological and immunophenotypical features are essential both for the correct diagnosis and to be able to classify this lesion among the corresponding eDCIS/solid papillary carcinoma of the breast, with neuroendocrine differentiation. Recent papers have attempted to shed light on the molecular features of EMPSGC, and much remains to be conducted in the attempt to subtype the molecular profiles of these entities. Future studies with large case series, and especially with molecular biology techniques, will be needed to further add information about EMPSGC and its relationship in the PCMC spectrum.